Metal-Organic Framework-Based Nanomedicine Platforms for Drug Delivery and Molecular Imaging - Cai, Wen; Chu, Cheng-Chao; Liu, Gang; Wáng, Yì-Xiáng J. (Small (Weinheim an der Bergstrasse, Germany), 2015)
Metal–organic frameworks (MOFs), which are a unique class of hybrid porous materials built from metal ions and organic linkers, have attracted significant research interest in recent years. Compared with conventional porous materials, MOFs exhibit a variety of advantages, including a large surface area, a tunable pore size and shape, an adjustable composition and structure, biodegradability, and versatile functionalities, which enable MOFs to perform as promising platforms for drug delivery, molecular imaging, and theranostic applications. In this article, the recent research progress related to nanoscale metal–organic frameworks (NMOFs) is summarized with a focus on synthesis strategies and drug delivery, molecular imaging, and theranostic applications. The future challenges and opportunities of NMOFs are also discussed in the context of translational medical research. More effort is warranted to develop clinically translatable NMOFs for various applications in nanomedicine. Nanoscale metal‐organic frameworks (NMOFs) are reviewed with a focus on the synthesis strategies and drug delivery, molecular imaging, and theranostic applications. The future challenges and opportunities of NMOFs in the context of translational medical research are systematically discussed.